2001
DOI: 10.1097/00004703-200110000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Mealtime Behaviors of Young Children: A Comparison of Normative and Clinical Data

Abstract: The objective of this study was to compare the behavior of healthy young children around feeding and mealtimes to the behavior of two clinical groups, children referred for feeding problems without related medical issues and those with medical issues associated with the feeding problems. Using the Behavioral Pediatrics Feeding Assessment Scale, data were obtained for 96 healthy children between the ages of 9 months and 7 years, and descriptive information is presented in the paper on these normal mealtime beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
256
4
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(289 citation statements)
references
References 19 publications
16
256
4
13
Order By: Relevance
“…The learning of this control also helped to mitigate the nausea and the need to spit before swallowing. We observed, according to the literature 15,16 , the importance of child autonomy during mealtimes and when this aspect can interfere with the quality of chewing and swallowing, in addition to all the sensory and emotional aspects involved in the act of eating.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The learning of this control also helped to mitigate the nausea and the need to spit before swallowing. We observed, according to the literature 15,16 , the importance of child autonomy during mealtimes and when this aspect can interfere with the quality of chewing and swallowing, in addition to all the sensory and emotional aspects involved in the act of eating.…”
Section: Resultsmentioning
confidence: 91%
“…bites and ideal amounts to be introduced to the oral cavity were worked on so that the patient could chew more comfortably. As BM had always been fed by other people, she could not learn how to control the necessary amount to be ingested for comfortable and efficient chewing, always receiving volumes that were too large for quick swallowing 16 . The learning of this control also helped to mitigate the nausea and the need to spit before swallowing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire has four stable domain scores referred to as child frequency score, parent frequency score (each derived from the sum of Likert responses), child problem score, and parent problem score (each derived from the sum of yes/no responses). It has previously been used in both clinical and non-clinical samples with Screening Avoidant/Restrictive Food Intake Disorder in Children 10 the primary aim to differentiate those children and families that have clinically significant feeding problems from those that do not (Crist & Napier-Philips, 2001). …”
Section: Behavioral Pediatric Feeding Assessment Scalementioning
confidence: 99%
“…Of the various psychometric scales that have been used to assess ARFID, only the Behavioral Pediatrics Feeding Assessment Scale (BPFAS; Crist et al, 1994) has shown consistent reliability and validity metrics, the ability to differentiating samples of clinical relevance from the general population (Crist & Napier-Philips., 2001;Dovey et al, 2013) and sensitivity to changes following intervention (Dovey & Martin, 2012a;Dovey & Martin, 2012b). Despite its favourable characteristics, the BPFAS is currently the longest, in terms of items to analyse, psychometric questionnaire available to clinicians who wish to screen for ARFID.…”
Section: Introductionmentioning
confidence: 99%